MATHEMATICAL MODELING OF BODY COOLING: AN APPROACH USING DIFFERENTIAL EQUATIONS - Pessoa, Samuel Moraes; Freire, Francielck Domingos; Mendes, Élys da Silva (Seven Editora, 2026)
Newton’s law of cooling is given as a mathematical model in the teaching of differential equations in higher education. It states that we can calculate the variation of temperature over time of a given body. This work associates mathematical modeling with differential equations through an experiment using Newton’s law. Topics such as the history of Newton’s law of cooling, ordinary differential equations, Newton’s law of cooling, mathematical modeling in physical phenomena, demonstration of the law, methodology for application, among others, will be addressed. The work aims to show the importance of mathematical modeling in the teaching of differential equations, especially Newton’s law presented in this work. Some methods for solving ordinary differential equations will also be presented, in order to show the importance of mathematics in the deduction of physical phenomena present in the daily life of an ordinary person.